MiFID II: regulating high frequency trading, other forms of algorithmic trading and direct electronic market access. Issue 2 (2nd April 2016) - Busch, Danny
Abstract : This article analyses and discusses the new MiFID II rules on high frequency trading (HFT), other forms of algorithmic trading (AT) and direct electronic market access (DEA). In particular, it discusses the benefits and risks of AT, HFT and DEA, the MiFID II definitions of these terms, the scope of the rules, as well as the applicable substantive rules.